2015
DOI: 10.1049/htl.2015.0028
|View full text |Cite
|
Sign up to set email alerts
|

Optical wireless connected objects for healthcare

Abstract: In this Letter the authors explore the communication capabilities of optical wireless technology for a wearable device dedicated to healthcare application. In an indoor environment sensible to electromagnetic perturbations such as a hospital, the use of optical wireless links can permit reducing the amount of radio frequencies in the patient environment. Moreover, this technology presents the advantage to be secure, low-cost and easy to deploy. On the basis of commercially available components, a custom-made w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…e authors in [15] experimentally confirmed the potentialities of IR system based on the diffuse configuration for mobile patient monitoring. Besides, a custom-made wearable device is presented in [16], which allows OWC-based transmission of accelerometer data in the context of physical activity supervision of poststroke patients in hospital. On the other hand, Alyan and Aljunid [17] and Chevalier et al [18] have proposed multiple access schemes based on CDMA spreading codes.…”
Section: Introductionmentioning
confidence: 99%
“…e authors in [15] experimentally confirmed the potentialities of IR system based on the diffuse configuration for mobile patient monitoring. Besides, a custom-made wearable device is presented in [16], which allows OWC-based transmission of accelerometer data in the context of physical activity supervision of poststroke patients in hospital. On the other hand, Alyan and Aljunid [17] and Chevalier et al [18] have proposed multiple access schemes based on CDMA spreading codes.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, in the indoor medical related system shown in the radiation intensity of the transmitter is modeled by the generalized Lambertian pattern as [1,2]:…”
Section: Lambertian and Non-lambertian Emission Patternmentioning
confidence: 99%
“…In typical indoor healthcare scenario, the OW channel gain form the optical transmitter on the patient to the optical receiver on the ceiling center could be expressed as [1,2]:…”
Section: Optical Wireless Link Characteristics Comparisonmentioning
confidence: 99%
See 2 more Smart Citations